Growing more with less: Breeding and developing drought resilient soybean to improve food security. (October 2019) - Dubey, Anamika; Kumar, Ashwani; Abd_Allah, Elsayed Fathi; Hashem, Abeer; Khan, Mohammed Latif
Highlights: Enhancing crop productivity under changing climatic conditions to meet the challenges of global food security is crucial. Drought stress is one of the main constraints that adversely affect soybean production. Plant growth promoting rhizobacteria played an important role in enhancing soybean production in sustainable manner. Advancement of omics technologies enabled us to unravel the role of these microbes in drought stress tolerance mechanism. Abstract: Soybean ( Glycine max L.) is considered an important crop, and enhancing its production under drought stress and changing climatic conditions to meet the challenges of global food security is crucial. Drought is considered one of the major abiotic factors that adversely affect soybean production. To address this challenge, we need to develop an integrative research approach that will bring together computational modelling, soil engineering, physiology, microbiology, molecular biology, genomics and plant breeding to study the underlying mechanisms of plant tolerance to drought stress. Advances in genomic technologies coupled with breeding approaches have helped scientists unravel the genes responsible for drought tolerance in crops. The success of a soybean breeding programme is largely dependent upon the extent of genetic variation in terms of drought tolerance-related traits. The availability of the whole soybean genome sequence is considered a major landmark in this process that will help design future strategies for improving soybean production. This review describes the recent advances in the study of the effect of drought stress on morpho-biochemical changes in soybean and the application of plant growth-promoting rhizobacteria, marker assisted selection, and different omics approaches to unravel the mechanism of drought tolerance. Here, in this review, we also highlight the customary knowledge on physiology, functional genomics and molecular breeding that may be significant in integrating genetic engineering and breeding approaches to improve drought tolerance in soybean crop.